Method for preparing high-weather-resistance solvent-free polyurethane from polycarbonate diol

By using a composite coating process consisting of BF-8021 water-based ultra-fast drying anti-corrosion resin and BF-9011 acrylic dispersion, the problem of insufficient rapid drying performance of water-based anti-corrosion paint is solved, improving construction efficiency and weather resistance, and reducing the risk of cost fluctuations.

CN120888240APending Publication Date: 2025-11-04XINJIANG QIANGRUN PAINT CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511155049.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-18
Publication Date
2025-11-04

AI Technical Summary

Technical Problem

Existing water-based anti-corrosion paints are not fast enough, resulting in low construction efficiency and susceptibility to external environmental factors, thus increasing the risk of cost fluctuations.

Method used

Using BF-8021 water-based ultra-fast drying anticorrosive resin and BF-9011 acrylic dispersion as core raw materials, combined with carbon black special dispersant, light calcium carbonate and barium sulfate, a composite coating is formed through a specific stirring and grinding process, which improves the drying speed and anticorrosive effect.

Benefits of technology

It achieves a surface drying speed of 10 minutes, a complete drying time of 40 minutes, no rusting or peeling after 200 hours of neutral salt spray testing, and no cracking or powdering after 200 hours of artificial aging. It meets the requirements of cast iron pipe paint to not rust, lose gloss, or peel off after 2 years of outdoor storage, thus reducing the risk of cost fluctuations.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120888240A_ABST
    Figure CN120888240A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of water-based paint preparation, and discloses a method for preparing high-weather-resistance solvent-free polyurethane from polycarbonate diol. The water-based paint is prepared from BF-8021 water-based ultrafast-drying anticorrosive resin, BF-9011 acrylic dispersion, a dispersing agent special for carbon black, carbon black, light calcium carbonate, barium sulfate, dimethylethanolamine, propylene glycol monomethyl ether, a defoaming agent, an anti-settling agent special for water-based paint, a drier special for water-based paint, texanol and water. The coating prepared by the invention has ultrafast drying speed, the drying speed of paint film surface drying is 10 minutes, and the hard drying time is 40 minutes; the paint film does not rust or fall off after the neutral salt spray test is carried out for 200h; after the paint is artificially aged for 200 hours, the paint film does not have the phenomena of cracking, powdering, bubbling, falling and rusting, the color difference E is 2.9, the gloss loss rate after water washing is 28%, the gloss loss rate after polishing is 8%, and the requirements that the cast pipe paint does not rust, does not lose gloss, does not fall off and the like after being stored outdoors for 2 years are met.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application relates to the technical field of water-based paint preparation, in particular to a method for preparing high-weather-resistance solvent-free polyurethane from polycarbonate diol. BACKGROUND

[0002] Polycarbonate diol (PCDL) can be used to prepare various high-performance low-viscosity resins due to its structural regularity and small molecular weight distribution, and the polycarbonate diol has excellent weather resistance and good elasticity and flexibility, and can be used to prepare flexible touch paint, which has the effects of low gloss, anti-glare, sound absorption, special elastic touch, impact resistance, scratch resistance and high weather resistance; the polycarbonate diol can be widely used on the surfaces of computer keyboards, U disks, mobile phones, electric hair dryer handles and electric tools, and can also be used for coating automobile interior parts; the superior mechanical properties, water decomposition resistance, heat resistance, chemical resistance and weather resistance of the polycarbonate diol make it have a wide application prospect in the industries of artificial leather, synthetic leather, elastomer, spandex, adhesive, automobile paint, touch paint, UV curing paint and UV resin synthesis.

[0003] Polycarbonate polyurethane represented by PCDL is considered to be the best in terms of heat resistance and hydrolysis resistance, and is widely used as a durable film or artificial leather for automobiles, (water-based) paint and adhesive;

[0004] For a long time, more than 90% of the anti-corrosion coatings of cast pipes at home and abroad are bitumen paint anti-corrosion coatings, and the cheapness and excellent water resistance of the bitumen paint make it irreplaceable in the application of cast pipes; however, the traditional bitumen coating has the defects of poor weather resistance, impact resistance and chemical resistance.

[0005] Therefore, in recent years, the state has improved the requirement for environmental protection, and water-based cast pipe paint has been widely used in the cast pipe industry.

[0006] Patent No. CN105778672A discloses an ultra-fast drying anti-adhesion cast pipe anti-corrosion coating, which is a solvent-based coating composed of thermoplastic acrylic resin liquid, petroleum resin liquid, modified polyurethane resin, dispersant, bentonite, iron black, barite powder, dimethylbenzene, cobalt naphthenate, chlorinated paraffin and leveling agent; compared with the traditional coating, the coating has the characteristics of normal temperature drying, ultra-fast drying, energy saving and consumption reduction, and meets the requirements of rapid coating process; the product can be stacked and packaged after being sprayed for 30 minutes at normal temperature without adhesion, is suitable for flow line operation, and the paint film does not fall off after mutual knocking during stacking, thereby solving the problems of aging of the paint film after being placed in the open air for a certain period of time, rusting of the cast pipe and the like; however, the weather resistance of the coating is affected by the presence of petroleum resin.

[0007] The application discloses CN109294408A discloses a kind of water-based cast pipe outer wall anticorrosive paint and preparation method thereof, discloses a kind of water-based cast pipe outer wall anticorrosive paint, by water-based epoxy ester resin, dispersing agent, defoaming agent, high-purity zinc phosphate, iron oxide black, ethylene glycol butyl ether, medium carbon black, wet silk mica, ultraviolet absorber, anticorrosive auxiliary agent, thickening agent composition;Solve the construction film thickness problem under the condition of cast pipe roughness, salt fog and aging problem and construction baking temperature problem;The component of the coating of the application has epoxy resin component, and there is a problem in the aspect of aging resistance, so ultraviolet absorber is added in it, but the fundamental problem cannot be solved;

[0008] The existing water-based anticorrosive paint still has obvious deficiencies in the performance of rapid drying, which leads to low construction efficiency and is easily affected by external environmental factors, thereby increasing the risk of cost fluctuation. SUMMARY

[0009] In view of the deficiencies of the prior art, the present application provides a method for preparing high-weather-resistant solvent-free polyurethane from polycarbonate diol, which solves the problem of the existing water-based anticorrosive paint still having obvious deficiencies in the performance of rapid drying, which leads to low construction efficiency and is easily affected by external environmental factors, thereby increasing the risk of cost fluctuation.

[0010] To achieve the above object, the present application is implemented by the following technical scheme: a method for preparing high-weather-resistant solvent-free polyurethane from polycarbonate diol, the high-weather-resistant solvent-free polyurethane comprising the following raw materials by weight: 10-45 parts of BF-8021 water-based super-fast drying anticorrosive resin, 5-25 parts of BF-9011 acrylic dispersion, 1-5 parts of carbon black special dispersant, 1-8 parts of carbon black, 5-25 parts of light calcium carbonate, 5-20 parts of barium sulfate, 5-15 parts of dimethyl ethanolamine, 5-20 parts of propylene glycol methyl ether, 1-6 parts of water-based paint special anti-settling agent, 0.2-2 parts of defoaming agent, 1-4 parts of water-based paint special drying agent, 1-6 parts of alcohol ester twelve, and 0-40 parts of water.

[0011] A method for preparing high-weather-resistant solvent-free polyurethane from polycarbonate diol, specifically comprising the following steps:

[0012] Step one, weigh BF-8021 water-based super-fast drying anticorrosive resin, BF-9011 acrylic dispersion, carbon black special dispersant, carbon black, light calcium carbonate, barium sulfate, dimethyl ethanolamine, propylene glycol methyl ether, defoaming agent, water-based paint special anti-settling agent, water-based paint special drying agent, alcohol ester twelve, and water, and prepare for use;

[0013] Step two, add BF-8021 water-based super-fast drying anticorrosive resin into the paint mixing tank, start stirring, control the speed at 500-700 r / min, and adjust the pH to 8-9 in two stages with dimethyl ethanolamine;

[0014] Step three, three-stage addition of carbon black special dispersant and carbon black, stirring speed control at 500-700 r / min, stirring 10 min;

[0015] Step four, in turn, add barium sulfate, light calcium carbonate and water-based paint special anti-settling agent, dispersion speed control 1500-1800 r / min, stirring 30 min;

[0016] Step five, sand mill using "three grinding method" to grind the raw materials to a fineness of less than 25 um, before sanding add 3% propylene glycol methyl ether to adjust the rheological properties;

[0017] Step six, in the paint tank, add BF-9011 acrylic dispersion, 97% propylene glycol methyl ether, defoamer, water-based paint special catalyst, alcohol ester twelve, adjust the viscosity with water;

[0018] Step seven, central control detection, after passing, filter packaging.

[0019] Preferably, in the said step two, two-stage adjustment of pH, the initial amount of dimethyl ethanolamine control at 70% of the total, pH to 7.5; after the BF-8021 water-based super-fast dry anticorrosive resin is completely wet, add the remaining 30% amine to pH 8.5, stirring 5 min.

[0020] Preferably, in the said step three, three-stage addition of carbon black special dispersant: first stage: first add 60% of the total dispersant, 500 r / min stirring 2 min; second stage: add carbon black, 600 r / min dispersion 5 min; third stage: add the remaining 40% of the dispersant, maintain 700 r / min stirring 3 min.

[0021] Preferably, in the said step four, first add barium sulfate, keep 800 r / min stirring 3 min, then light calcium carbonate and water-based paint special anti-settling agent are added synchronously, and the stirring speed is maintained at 800 r / min for 5 min, finally the dispersion speed is controlled in stages: first stage: 1500 r / min stirring 8 min; second stage: 1800 r / min stirring 14 min.

[0022] Preferably, in the said step five, using "three grinding method": first pass: coarse grinding using 0.8 mm zirconium beads; second pass: medium grinding using 0.6 mm zirconium beads; third pass: fine grinding using 0.3 mm zirconium beads; sample after each grinding to measure fineness, change bead diameter after reaching the standard.

[0023] Preferably, in the said step six, the defoamer is divided into three batches: 70% is added after grinding, 20% is added during paint mixing, and 10% is added before packaging;

[0024] The special catalyst for water-based paint is mixed with alcohol ester twelve at 1:1, then is added dropwise at a speed of 2-3 mL / min, and a water bath temperature control of 30±2 DEG C is added; the viscosity adjustment is changed to three-stage water supplement: water supplement after grinding to 20 s, water supplement after grinding to 30 s, and water supplement before packaging to 35 s.

[0025] Preferably, in the step seven, the filtration adopts 200 mesh and 5 mu m double-layer filter cloth.

[0026] The application provides a method for preparing high-weather-resistance solvent-free polyurethane from polycarbonate diol.

[0027] The high-weather-resistance solvent-free polyurethane prepared by the method has the following advantages compared with the prior art:

[0028] The BF-8021 water-based super-fast-drying anti-corrosion resin and the BF-9011 acrylic dispersion are used as core raw materials, and the two jointly form a composite coating, effectively improving the anti-corrosion effect, greatly shortening the drying time, maintaining good physical and chemical properties, and reducing the cost fluctuation risk; the special catalyst for water-based paint matches the fast-drying characteristics of the alcohol ester twelve resin, shortens the real drying time; in addition, light calcium carbonate and barium sulfate are specially added in the formula to ensure that the paint has good leveling and sedimentation control, prevents the coating from cracking, solves the dispersion problem of carbon black in the paint and the flocculation problem of carbon black, ensures the dark color of the paint film, and makes the cast pipe paint still not rust, not lose light, and not fall off after being stored outdoors for 2 years. BRIEF DESCRIPTION OF DRAWINGS

[0029] Figure 1 The figure is a flowchart of the method. DETAILED DESCRIPTION

[0030] The technical solutions in the embodiments of the application will be clearly and completely described below with reference to the drawings in the embodiments of the application. Obviously, the described embodiments are only part of the embodiments of the application, rather than all the embodiments of the application. Based on the embodiments in the application, all other embodiments obtained by those skilled in the art without creative labor fall within the protection scope of the application.

[0031] Embodiment one

[0032] Please refer to Figure 1The application provides a method for preparing high-weather-resistance solvent-free polyurethane from polycarbonate diol, which comprises the following raw materials in parts by weight: 25 parts of BF-8021 water-based super-fast-drying anticorrosive resin, 25 parts of BF-9011 acrylic dispersion, 2 parts of carbon black special dispersant, 6 parts of carbon black, 15 parts of light calcium carbonate, 10 parts of barium sulfate, 5 parts of dimethyl ethanolamine, 15 parts of propylene glycol methyl ether, 1 part of water-based paint special anti-settling agent, 0.8 parts of defoaming agent, 2 parts of water-based paint special drying agent, 3 parts of alcohol ester twelve and 15 parts of water.

[0033] The BF-8021 water-based super-fast-drying anticorrosive resin, one of the main film-forming substances, has the technical indexes shown in Table 1.

[0034] Table 1, technical indexes of the BF-8021 water-based super-fast-drying anticorrosive resin

[0035] Detection item Detection content Appearance Clear and transparent liquid Color, number, Fe-Co colorimeter ≤ 8 Solid content, % 120℃, 2h 70±2 Viscosity capillary, s 25℃ 50-90 Acid value, mgKOH / g 20-30

[0036] The BF-9011 acrylic dispersion, another main film-forming substance, is a self-crosslinking surfactant-free acrylic dispersion, which can provide excellent hardness, chemical resistance and easy sandability; the main performance indexes are shown in Table 2.

[0037] Table 2, technical indexes of the BF-9011 acrylic dispersion

[0038] Index Detection value Detection standard Appearance Translucent milky white solution GB / T 9761-2008 Solid content, % 40±1 GB / T 1725-2007 pH (25℃) 7.5-8.5 GB 8325-1987 Specific gravity, g.cm-3 1.04 GB / T 6750-2007 Viscosity (25℃), mPa.s ≤500 GB / T 2794-2013 Minimum film forming temperature, ℃ 35 GB / T9267-2008

[0039] The application further discloses a method for preparing high-weather-resistance solvent-free polyurethane from polycarbonate diol, which specifically comprises the following steps.

[0040] In step one, the BF-8021 water-based super-fast-drying anticorrosive resin, the BF-9011 acrylic dispersion, the carbon black special dispersant, the carbon black, the light calcium carbonate, the barium sulfate, the dimethyl ethanolamine, the propylene glycol methyl ether, the defoaming agent, the water-based paint special anti-settling agent, the water-based paint special drying agent, the alcohol ester twelve and the water are weighed and prepared;

[0041] The BF-8021 water-based super-fast-drying anticorrosive resin is placed in a constant-temperature tank for 2 hours in advance, the temperature is controlled at 25 DEG C, and the frozen resin is thawed and filtered in circulation to remove impurities possibly precipitated in the thawing process, so that the problem that the temperature fluctuation of the resin affects the initial viscosity is solved;

[0042] In step two, the BF-8021 water-based super-fast-drying anticorrosive resin is added into a paint mixing tank, and stirring is started, the stirring speed is controlled at 500-700 r / min, and the pH value is adjusted to 8-9 by using dimethyl ethanolamine in two stages;

[0043] Two-stage pH adjustment, the initial amount of dimethyl ethanolamine is controlled at 70% of the total amount, and the pH is adjusted to 7.5; after the BF-8021 water-based super-fast dry preservative resin is completely wetted, the remaining 30% amine is added to adjust the pH to 8.5, and stirred for 5 minutes; to prevent local excessive alkalinity from causing resin gelation, the pH is adjusted in stages to improve pH stability;

[0044] Step three, three-stage addition of carbon black special dispersant and carbon black, stirring speed control at 500-700r / min, stirring for 10 minutes;

[0045] Three-stage addition of carbon black special dispersant: first stage: add 60% of the total amount of dispersant first, stir at 500r / min for 2 minutes; second stage: add carbon black, disperse at 600r / min for 5 minutes; third stage: add the remaining 40% of the dispersant, maintain stirring at 700r / min for 3 minutes; segmented addition can form a more stable adsorption layer, reducing the surface tension of the system;

[0046] Step four, add barium sulfate, light calcium carbonate and water-based paint special anti-settling agent in turn, and control the dispersion speed in stages at 1500-1800r / min, and stir for 30 minutes;

[0047] First add barium sulfate, maintain stirring at 800r / min for 3 minutes, then add light calcium carbonate and water-based paint special anti-settling agent synchronously, and maintain stirring speed at 800r / min for 5 minutes, finally control the dispersion speed in stages: first stage: 1500r / min for 8 minutes; second stage: 1800r / min for 14 minutes; adding high-density fillers first can reduce the risk of stratification during stirring; anti-settling agent and fillers are dispersed synchronously to form a more stable network structure; step-up speed avoids powder splashing;

[0048] Step five, use a sand mill to grind the raw materials to a fineness of less than 25um by "three grinding method"; add 3% propylene glycol methyl ether before sanding to adjust the rheological properties; "three grinding method": first pass: coarse grinding with 0.8mm zirconium beads; second pass: medium grinding with 0.6mm zirconium beads; third pass: fine grinding with 0.3mm zirconium beads; take samples after each grinding to measure fineness, and change bead diameter after reaching the standard; stepwise grinding can improve efficiency; solvent adjustment can improve the thixotropy of the slurry and reduce the fineness;

[0049] Step six, in the paint mixing tank, add BF-9011 acrylic dispersion, 97% propylene glycol methyl ether, defoamer, water-based paint special catalyst, and alcohol ester twelve, and adjust the viscosity with water;

[0050] The defoamer is added in three batches: 70% after grinding, 20% during paint mixing, and 10% before packaging;

[0051] Adding defoaming agent in three times can deal with different stages of foam production; the special drier for water-based paint is mixed with alcohol ester twelve at a ratio of 1:1 in advance, then added dropwise at a speed of 2-3 mL / min, and a water bath temperature control of 30±2℃ is added; pre-mixing improves the drier efficiency, and temperature control dropwise avoids local over-concentration of the drier;

[0052] The viscosity adjustment is changed to three-stage water supplement: water supplement after grinding to 20s, water supplement after grinding to 30s, and water supplement before packaging to 35s; segmented water supplement prevents paint film shrinkage;

[0053] Step seven, control detection, and after passing, filter packaging; filter with 200 mesh + 5 μm double-layer filter cloth; double-layer filtration prevents impurity residues.

[0054] Example two:

[0055] Please refer to Figure 1 The application provides a method for preparing high-weather-resistant solvent-free polyurethane from polycarbonate diol, which comprises the following raw materials in parts by weight: 35 parts of BF-8021 water-based super-fast drying anticorrosive resin, 10 parts of BF-9011 acrylic dispersion, 4 parts of carbon black special dispersant, 8 parts of carbon black, 25 parts of light calcium carbonate, 8 parts of barium sulfate, 8 parts of dimethyl ethanolamine, 12 parts of propylene glycol methyl ether, 3 parts of water-based paint special anti-settling agent, 0.6 parts of defoaming agent, 4 parts of water-based paint special drier, 6 parts of alcohol ester twelve, and 35 parts of water.

[0056] The application also discloses a method for preparing high-weather-resistant solvent-free polyurethane from polycarbonate diol, which specifically comprises the following steps:

[0057] Step one, weighing BF-8021 water-based super-fast drying anticorrosive resin, BF-9011 acrylic dispersion, carbon black special dispersant, carbon black, light calcium carbonate, barium sulfate, dimethyl ethanolamine, propylene glycol methyl ether, defoaming agent, water-based paint special anti-settling agent, water-based paint special drier, alcohol ester twelve, and water, and reserving;

[0058] The BF-8021 water-based super-fast drying anticorrosive resin is placed in a constant-temperature tank 2 hours in advance, the temperature is controlled at 25℃, and the frozen resin is circularly stirred and filtered to remove impurities possibly precipitated in the freezing process; the problem that temperature fluctuation of the resin affects the initial viscosity is solved;

[0059] Step two, adding BF-8021 water-based super-fast drying anticorrosive resin in a paint mixing tank, and stirring at a speed of 500-700 r / min, and adjusting the pH value to 8-9 by using dimethyl ethanolamine in two stages;

[0060] Two-stage pH adjustment, the initial amount of dimethyl ethanolamine is controlled at 70% of the total amount, and the pH is adjusted to 7.5; after the BF-8021 water-based super-fast dry preservative resin is completely wetted, the remaining 30% amine is added to adjust the pH to 8.5, and stirred for 5 min; to prevent local excessive alkalinity from causing resin gelation, the pH is adjusted in stages to improve pH stability;

[0061] Step three, three-stage addition of carbon black special dispersant and carbon black, stirring speed control at 500-700r / min, stirring for 10 min;

[0062] Three-stage addition of carbon black special dispersant: first stage: add 60% of the total amount of dispersant first, stir at 500r / min for 2 min; second stage: add carbon black, disperse at 600r / min for 5 min; third stage: add the remaining 40% of the dispersant, maintain stirring at 700r / min for 3 min; segmented addition can form a more stable adsorption layer, reducing the surface tension of the system;

[0063] Step four, add barium sulfate, light calcium carbonate and water-based paint special anti-settling agent in turn, and control the dispersion speed in stages at 1500-1800r / min, stirring for 30 min;

[0064] First add barium sulfate, maintain stirring at 800r / min for 3 min, then add light calcium carbonate and water-based paint special anti-settling agent synchronously, and maintain stirring speed at 800r / min for 5 min, finally control the dispersion speed in stages: first stage: 1500r / min for 8 min; second stage: 1800r / min for 14 min; adding high-density fillers first can reduce the risk of stratification during stirring; anti-settling agent and fillers are dispersed synchronously to form a more stable network structure; step-up speed avoids powder splashing;

[0065] Step five, use a sand mill to grind the raw materials to a fineness of less than 25um by "three-pass grinding method"; add 3% propylene glycol methyl ether before sanding to adjust the rheological properties; "three-pass grinding method": first pass: coarse grinding with 0.8mm zirconium beads; second pass: medium grinding with 0.6mm zirconium beads; third pass: fine grinding with 0.3mm zirconium beads; take samples after each grinding to measure fineness, and change the bead diameter when the standard is met; stepwise grinding can improve efficiency; solvent adjustment can improve the thixotropy of the slurry and reduce the fineness;

[0066] Step six, in the paint mixing tank, add BF-9011 acrylic dispersion, 97% propylene glycol methyl ether, defoamer, water-based paint special catalyst, and alcohol ester twelve, and adjust the viscosity with water;

[0067] The defoamer is added in three batches: 70% after grinding, 20% during paint mixing, and 10% before packaging; adding the defoamer in three times can deal with the foam produced at different stages;

[0068] The special catalyst for water-based paint is mixed with alcohol ester twelve at a ratio of 1:1, then added dropwise at a speed of 2-3 mL / min, and a water bath temperature control of 30±2℃ is added; the pre-mixing improves the catalytic efficiency, and the temperature control dropwise addition avoids local over-concentration of the catalyst;

[0069] The viscosity adjustment is changed to three-stage water supplement: water supplement after grinding to 20s, water supplement after grinding to 30s, and water supplement before packaging to 35s; segmented water supplement prevents paint film shrinkage;

[0070] Step seven, control detection, and after passing, filter packaging; filter with 200 mesh + 5 μm double-layer filter cloth; double-layer filtration prevents impurity residues.

[0071] Example three:

[0072] Please refer to Figure 1 The application provides a method for preparing high-weather-resistant solvent-free polyurethane from polycarbonate diol, which comprises the following raw materials in parts by weight: 15 parts of BF-8021 water-based super-fast drying anticorrosive resin, 20 parts of BF-9011 acrylic dispersion, 1 part of carbon black special dispersant, 4 parts of carbon black, 13 parts of light calcium carbonate, 16 parts of barium sulfate, 12 parts of dimethyl ethanolamine, 16 parts of propylene glycol methyl ether, 2 parts of water-based paint special anti-settling agent, 1 part of defoaming agent, 4 parts of water-based paint special catalyst, 6 parts of alcohol ester twelve, and 22 parts of water.

[0073] The application also discloses a method for preparing high-weather-resistant solvent-free polyurethane from polycarbonate diol, which specifically comprises the following steps:

[0074] Step one, weigh BF-8021 water-based super-fast drying anticorrosive resin, BF-9011 acrylic dispersion, carbon black special dispersant, carbon black, light calcium carbonate, barium sulfate, dimethyl ethanolamine, propylene glycol methyl ether, defoaming agent, water-based paint special anti-settling agent, water-based paint special catalyst, alcohol ester twelve, and water, and prepare them for use;

[0075] The BF-8021 water-based super-fast drying anticorrosive resin is placed in a constant-temperature tank 2 hours in advance, the temperature is controlled at 25℃, and the frozen resin is circularly stirred and filtered to remove impurities that may be precipitated during the thawing process; the problem that temperature fluctuation of the resin affects the initial viscosity is solved;

[0076] Step two, add the BF-8021 water-based super-fast drying anticorrosive resin into a paint mixing tank, start stirring, control the stirring speed at 500-700 r / min, and adjust the pH value to 8-9 by using dimethyl ethanolamine in two stages;

[0077] Two-stage pH adjustment, the initial amount of dimethyl ethanolamine is controlled at 70% of the total amount, and the pH is adjusted to 7.5; after the BF-8021 water-based super-fast dry preservative resin is completely wetted, the remaining 30% amine is added to adjust the pH to 8.5, and stirred for 5 minutes; to prevent local excessive alkalinity from causing resin gelation, the pH is adjusted in stages to improve pH stability;

[0078] Step three, three-stage addition of carbon black special dispersant and carbon black, stirring speed control at 500-700r / min, stirring for 10 minutes;

[0079] Three-stage addition of carbon black special dispersant: first stage: add 60% of the total amount of dispersant first, stir at 500r / min for 2 minutes; second stage: add carbon black, disperse at 600r / min for 5 minutes; third stage: add the remaining 40% of the dispersant, maintain stirring at 700r / min for 3 minutes; segmented addition can form a more stable adsorption layer, reducing the surface tension of the system;

[0080] Step four, add barium sulfate, light calcium carbonate and water-based paint special anti-settling agent in turn, and control the dispersion speed in stages at 1500-1800r / min, and stir for 30 minutes;

[0081] First add barium sulfate, maintain stirring at 800r / min for 3 minutes, then add light calcium carbonate and water-based paint special anti-settling agent synchronously, and maintain the stirring speed at 800r / min for 5 minutes, finally control the dispersion speed in stages: first stage: stir at 1500r / min for 8 minutes; second stage: stir at 1800r / min for 14 minutes; adding high-density fillers first can reduce the risk of stratification during stirring; anti-settling agent and fillers are dispersed synchronously to form a more stable network structure; step-up speed avoids powder splashing;

[0082] Step five, use "three-pass grinding method" to grind the raw materials to a fineness of less than 25um in a sand mill, and add 3% propylene glycol methyl ether before grinding to adjust the rheological properties; "three-pass grinding method": first pass: coarse grinding with 0.8mm zirconium beads; second pass: medium grinding with 0.6mm zirconium beads; third pass: fine grinding with 0.3mm zirconium beads; take samples after each pass of grinding to measure fineness, and change the bead diameter after meeting the standard; stepwise grinding can improve efficiency; solvent adjustment can improve the thixotropy of the slurry and reduce the fineness;

[0083] Step six, in the paint mixing tank, add BF-9011 acrylic dispersion, 97% propylene glycol methyl ether, defoamer, water-based paint special catalyst, and alcohol ester twelve, and adjust the viscosity with water;

[0084] The defoaming agent is added in three batches: 70% after grinding, 20% during the paint mixing stage, and 10% before packaging; the defoaming agent is added in three times to deal with the foam generated in different stages; the special catalyst for water-based paint is mixed with alcohol ester twelve at a ratio of 1:1 in advance, and then added dropwise at a speed of 2-3 mL / min, and a water bath temperature control of 30±2℃ is added; the pre-mixing improves the catalytic efficiency, and the temperature control dropwise addition avoids the local over-concentration of the catalyst; the viscosity adjustment is changed to three-stage water supplement: water supplement to 20s after grinding, water supplement to 30s after grinding, and water supplement to 35s before packaging; the segmented water supplement prevents the shrinkage of the paint film;

[0085] Step seven, control detection, qualified, filter packaging; filter with 200 mesh + 5 μm double-layer filter cloth; double-layer filtration prevents impurities from remaining.

[0086] Example four:

[0087] Please refer to Figure 1 The application provides a method for preparing high-weather-resistant solvent-free polyurethane from polycarbonate diol, which comprises the following raw materials in parts by weight: 44 parts of BF-8021 water-based super-fast drying anticorrosive resin, 8 parts of BF-9011 acrylic dispersion, 3 parts of carbon black special dispersant, 7 parts of carbon black, 23 parts of light calcium carbonate, 15 parts of barium sulfate, 10 parts of dimethyl ethanolamine, 16 parts of propylene glycol methyl ether, 2 parts of water-based paint special anti-settling agent, 2 parts of defoaming agent, 4 parts of water-based paint special catalyst, 5.5 parts of alcohol ester twelve, and 32 parts of water.

[0088] The application also discloses a method for preparing high-weather-resistant solvent-free polyurethane from polycarbonate diol, which specifically comprises the following steps:

[0089] Step one, weighing BF-8021 water-based super-fast drying anticorrosive resin, BF-9011 acrylic dispersion, carbon black special dispersant, carbon black, light calcium carbonate, barium sulfate, dimethyl ethanolamine, propylene glycol methyl ether, defoaming agent, water-based paint special anti-settling agent, water-based paint special catalyst, alcohol ester twelve and water, and reserving;

[0090] The BF-8021 water-based super-fast drying anticorrosive resin is placed in a constant-temperature tank 2 hours in advance, the temperature is controlled at 25℃, and the frozen resin is circularly stirred and filtered to remove impurities possibly precipitated in the thawing process; the temperature fluctuation of the resin can affect the initial viscosity;

[0091] Step two, adding the BF-8021 water-based super-fast drying anticorrosive resin into a paint mixing tank, and stirring at a speed of 500-700 r / min, and adjusting the pH value to 8-9 by using dimethyl ethanolamine in two stages;

[0092] Two-stage pH adjustment, initial dimethyl ethanolamine amount control at 70% of the total, pH to 7.5; after the BF-8021 water-based super-fast dry preservative resin is completely wet, add the remaining 30% amine to pH 8.5, stir for 5 min; prevent local excessive alkalinity from causing resin gel, and adjust the pH in stages to improve pH stability;

[0093] Step three, three-stage addition of carbon black special dispersant and carbon black, stirring speed control at 500-700r / min, stirring for 10 min;

[0094] Three-stage addition of carbon black special dispersant: first stage: add 60% of the total dispersant first, stir at 500r / min for 2 min; second stage: add carbon black, disperse at 600r / min for 5 min; third stage: add the remaining 40% of the dispersant, maintain stirring at 700r / min for 3 min; segmented addition can form a more stable adsorption layer, reducing the surface tension of the system;

[0095] Step four, add barium sulfate, light calcium carbonate and water-based paint special anti-settling agent in turn, disperse the speed in stages control 1500-1800r / min, stirring for 30 min;

[0096] First add barium sulfate, keep stirring at 800r / min for 3 min, then add light calcium carbonate and water-based paint special anti-settling agent synchronously, and maintain the stirring speed at 800r / min for 5 min, finally use the disperse speed in stages control: first stage: 1500r / min stirring for 8 min; second stage: 1800r / min stirring for 14 min; high-density filler is added first to reduce the risk of stratification during stirring; anti-settling agent and filler are dispersed synchronously to form a more stable network structure; segmented speed increase avoids powder splashing;

[0097] Step five, use "three-pass grinding method" to grind the raw materials to a fineness of less than 25um in a sand mill, add 3% propylene glycol methyl ether before sanding to adjust the rheological properties; "three-pass grinding method": first pass: coarse grinding with 0.8mm zirconium beads; second pass: medium grinding with 0.6mm zirconium beads; third pass: fine grinding with 0.3mm zirconium beads; take samples after each pass of grinding to measure fineness, and change the bead diameter after meeting the standard; stepwise grinding can improve efficiency; solvent adjustment can improve the thixotropy of the slurry and reduce the fineness;

[0098] Step six, in the paint mixing tank, add BF-9011 acrylic dispersion, 97% propylene glycol methyl ether, defoamer, water-based paint special catalyst, alcohol ester twelve, and adjust the viscosity with water;

[0099] The defoaming agent is added in three batches: 70% after grinding, 20% during the paint mixing stage, and 10% before packaging; adding the defoaming agent in three times can deal with the foam produced in different stages; the special catalyst for water-based paint is mixed with alcohol ester twelve at a ratio of 1:1 in advance, and then added dropwise at a speed of 2-3 mL / min, and a water bath temperature control of 30±2℃ is added; pre-mixing improves the catalytic efficiency, and temperature control and dropwise addition avoid local over-concentration of the catalyst; viscosity adjustment is changed to three-stage water supplement: water supplement to 20s after grinding, water supplement to 30s after grinding, and water supplement to 35s before packaging; segmented water supplement prevents shrinkage holes in the paint film.

[0100] Step seven, control detection, qualified, filter packaging; filter with 200 mesh + 5 μm double-layer filter cloth; double-layer filtration prevents impurities from remaining.

[0101] Example five:

[0102] Please refer to Figure 1 The application provides a method for preparing high-weather-resistant solvent-free polyurethane from polycarbonate diol, which comprises the following raw materials in parts by weight: 12 parts of BF-8021 water-based super-fast drying anticorrosive resin, 23 parts of BF-9011 acrylic dispersion, 2 parts of carbon black special dispersant, 4 parts of carbon black, 21 parts of light calcium carbonate, 14 parts of barium sulfate, 6 parts of dimethyl ethanolamine, 8 parts of propylene glycol methyl ether, 2 parts of water-based paint special anti-settling agent, 1.6 parts of defoaming agent, 4 parts of water-based paint special catalyst, 2 parts of alcohol ester twelve, and 35 parts of water.

[0103] The application also discloses a method for preparing high-weather-resistant solvent-free polyurethane from polycarbonate diol, which specifically comprises the following steps:

[0104] Step one, weighing BF-8021 water-based super-fast drying anticorrosive resin, BF-9011 acrylic dispersion, carbon black special dispersant, carbon black, light calcium carbonate, barium sulfate, dimethyl ethanolamine, propylene glycol methyl ether, defoaming agent, water-based paint special anti-settling agent, water-based paint special catalyst, alcohol ester twelve and water, and reserving;

[0105] The BF-8021 water-based super-fast drying anticorrosive resin is placed in a constant-temperature tank 2 hours in advance, the temperature is controlled at 25℃, and the frozen resin is circularly stirred and filtered to remove impurities possibly precipitated in the thawing process; the problem that temperature fluctuation of the resin affects the initial viscosity is solved;

[0106] Step two, adding the BF-8021 water-based super-fast drying anticorrosive resin into a paint mixing tank, and stirring at a speed of 500-700 r / min, and adjusting the pH value to 8-9 by using dimethyl ethanolamine in two stages;

[0107] Two-stage pH adjustment, initial dimethyl ethanolamine amount control at 70% of the total, pH to 7.5; after the BF-8021 water-based super-fast dry preservative resin is completely wet, add the remaining 30% amine to pH 8.5, stir for 5 min; prevent local excessive alkalinity from causing resin gel, and adjust the pH in stages to improve pH stability;

[0108] Step three, three-stage addition of carbon black special dispersant and carbon black, stirring speed control at 500-700r / min, stirring for 10 min;

[0109] Three-stage addition of carbon black special dispersant: first stage: add 60% of the total dispersant first, stir at 500r / min for 2 min; second stage: add carbon black, disperse at 600r / min for 5 min; third stage: add the remaining 40% of the dispersant, maintain stirring at 700r / min for 3 min; segmented addition can form a more stable adsorption layer, reducing the surface tension of the system;

[0110] Step four, add barium sulfate, light calcium carbonate and water-based paint special anti-settling agent in turn, disperse the speed in stages control 1500-1800r / min, stirring for 30 min;

[0111] First add barium sulfate, maintain stirring at 800r / min for 3 min, then add light calcium carbonate and water-based paint special anti-settling agent synchronously, and maintain stirring speed at 800r / min for 5 min, finally use the disperse speed in stages control: first stage: 1500r / min stirring for 8 min; second stage: 1800r / min stirring for 14 min; high-density filler is added first to reduce the risk of stratification during stirring; anti-settling agent and filler are dispersed synchronously to form a more stable network structure; segmented speed increase avoids powder splashing;

[0112] Step five, use "three-pass grinding method" to grind the raw materials to a fineness of less than 25um in a sand mill, add 3% propylene glycol methyl ether before sanding to adjust the rheological properties; "three-pass grinding method": first pass: coarse grinding with 0.8mm zirconium beads; second pass: medium grinding with 0.6mm zirconium beads; third pass: fine grinding with 0.3mm zirconium beads; take samples after each pass of grinding to measure fineness, and change the bead diameter after meeting the standard; stepwise grinding can improve efficiency; solvent adjustment can improve the thixotropy of the slurry and reduce the fineness;

[0113] Step six, in the paint mixing tank, add BF-9011 acrylic dispersion, 97% propylene glycol methyl ether, defoamer, water-based paint special catalyst, alcohol ester twelve, and adjust the viscosity with water;

[0114] Defoaming agent is added in three batches: 70% after grinding, 20% during paint mixing, and 10% before packaging; adding defoaming agent in three times can deal with different stages of foam production; the special catalyst for water-based paint is mixed with alcohol ester twelve at a ratio of 1:1 in advance, then added dropwise at a speed of 2-3 mL / min, and the water bath temperature is controlled at 30±2℃; pre-mixing improves the catalytic efficiency, and temperature-controlled dropping avoids local over-concentration of the catalyst; viscosity adjustment is changed to three-stage water supplement: water supplement to 20s after grinding, water supplement to 30s after grinding, and water supplement to 35s before packaging; segmented water supplement prevents paint film shrinkage;

[0115] Step seven, control detection, qualified, filter packaging; filter with 200 mesh + 5 μm double-layer filter cloth; double-layer filtration prevents impurities from remaining.

[0116] Example six:

[0117] Please refer to Figure 1 The application provides a method for preparing high-weather-resistant solvent-free polyurethane from polycarbonate diol, which comprises the following raw materials in parts by weight: 43 parts of BF-8021 water-based super-fast drying anticorrosive resin, 12 parts of BF-9011 acrylic dispersion, 5 parts of carbon black special dispersant, 8 parts of carbon black, 23 parts of light calcium carbonate, 10 parts of barium sulfate, 9 parts of dimethyl ethanolamine, 6 parts of propylene glycol methyl ether, 2 parts of water-based paint special anti-settling agent, 0.8 parts of defoaming agent, 4 parts of water-based paint special catalyst, 2 parts of alcohol ester twelve, and 35 parts of water.

[0118] The application also discloses a method for preparing high-weather-resistant solvent-free polyurethane from polycarbonate diol, which specifically comprises the following steps:

[0119] Step one, weighing BF-8021 water-based super-fast drying anticorrosive resin, BF-9011 acrylic dispersion, carbon black special dispersant, carbon black, light calcium carbonate, barium sulfate, dimethyl ethanolamine, propylene glycol methyl ether, defoaming agent, water-based paint special anti-settling agent, water-based paint special catalyst, alcohol ester twelve and water, and reserving;

[0120] The BF-8021 water-based super-fast drying anticorrosive resin is placed in a constant-temperature tank 2 hours in advance, the temperature is controlled at 25℃, and the frozen resin is circularly stirred and filtered to remove impurities possibly precipitated in the thawing process; the temperature fluctuation of the resin can affect the initial viscosity;

[0121] Step two, adding BF-8021 water-based super-fast drying anticorrosive resin in a paint mixing tank, stirring at a speed of 500-700 r / min, and adjusting the pH value to 8-9 by using dimethyl ethanolamine in two stages;

[0122] Two-stage pH adjustment, initial dimethyl ethanolamine amount control at 70% of the total, pH to 7.5; after the BF-8021 water-based super-fast dry preservative resin is completely wet, add the remaining 30% amine to pH 8.5, stir for 5 min; prevent local excessive alkalinity from causing resin gel, and adjust the pH in stages to improve pH stability;

[0123] Step three, three-stage addition of carbon black special dispersant and carbon black, stirring speed control at 500-700r / min, stirring for 10 min;

[0124] Three-stage addition of carbon black special dispersant: first stage: add 60% of the total dispersant first, stir at 500r / min for 2 min; second stage: add carbon black, disperse at 600r / min for 5 min; third stage: add the remaining 40% of the dispersant, maintain stirring at 700r / min for 3 min; segmented addition can form a more stable adsorption layer, reducing the surface tension of the system;

[0125] Step four, add barium sulfate, light calcium carbonate and water-based paint special anti-settling agent in turn, disperse the speed in stages control 1500-1800r / min, stirring for 30 min;

[0126] First add barium sulfate, keep stirring at 800r / min for 3 min, then add light calcium carbonate and water-based paint special anti-settling agent synchronously, and maintain the stirring speed at 800r / min for 5 min, finally use the disperse speed in stages control: first stage: 1500r / min stirring for 8 min; second stage: 1800r / min stirring for 14 min; high-density filler is added first to reduce the risk of stratification during stirring; anti-settling agent and filler are dispersed synchronously to form a more stable network structure; segmented speed increase avoids powder splashing;

[0127] Step five, use "three-pass grinding method" to grind the raw materials to a fineness of less than 25um in a sand mill, add 3% propylene glycol methyl ether before sanding to adjust the rheological properties; "three-pass grinding method": first pass: coarse grinding with 0.8mm zirconium beads; second pass: medium grinding with 0.6mm zirconium beads; third pass: fine grinding with 0.3mm zirconium beads; take samples after each pass of grinding to measure fineness, and change the bead diameter after meeting the standard; stepwise grinding can improve efficiency; solvent adjustment can improve the thixotropy of the slurry and reduce the fineness;

[0128] Step six, in the paint mixing tank, add BF-9011 acrylic dispersion, 97% propylene glycol methyl ether, defoamer, water-based paint special catalyst, alcohol ester twelve, and adjust the viscosity with water;

[0129] Defoaming agent is added in three batches: 70% after grinding, 20% during paint mixing, and 10% before packaging; adding defoaming agent in three times can deal with different stages of foam production; special water-based paint drier is mixed with alcohol ester twelve at a ratio of 1:1 before dropping, at a speed of 2-3 mL / min, and with water bath temperature control at 30±2℃; pre-mixing improves the drier efficiency, and temperature control dropping avoids local over-concentration of the drier; viscosity adjustment is changed to three-stage water supplement: water supplement after grinding to 20s, water supplement after grinding to 30s, and water supplement before packaging to 35s; segmented water supplement prevents paint film shrinkage;

[0130] Step seven, control detection, qualified, filter packaging; filter uses 200 mesh + 5 μm double-layer filter cloth; double-layer filtration prevents impurity residues.

[0131] Test the above examples:

[0132] Drying time test, neutral salt spray test, and artificial accelerated aging test are conducted on the paint film;

[0133] Among them, the drying time test conditions are: in an environment of 25-30℃; the judgment standard is: the drying speed of the paint film surface ≤10min, and the real drying time ≤40min;

[0134] The neutral salt spray test conditions are: 5% sodium chloride solution pH=6.5-7.2, temperature 35℃±1℃, continuous spraying for 200h; the judgment standard is: the paint film does not rust or fall off;

[0135] The artificial accelerated aging test conditions are: xenon lamp aging test machine, irradiation intensity 0.51W / m²(340nm), temperature 65℃±3℃, humidity 50%±5%, water spraying cycle 18min / 102min, cycle 200h, tested by spectrophotometer; the judgment standard is: the paint film has no cracking, powdering, blistering, falling off, rusting, etc., color difference △E≤3.0, gloss loss rate after washing ≤30%, gloss loss rate after polishing ≤10%.

[0136] Drying time test Neutral salt spray test Artificial accelerated aging test Example one Table dry 12min, real dry 48h (catalyst 2 parts, alcohol ester twelve 3 parts, drying speed is slow) 168h appear small rust point (BF-8021 resin 25 parts, insufficient corrosion resistance) △E=3.5 (over standard), gloss loss rate after washing 35% (over standard), gloss loss rate after polishing 10% (meet the requirements) Example two Table dry 8min, real dry 36h (catalyst 4 parts, drying speed is good) 192h no rust (BF-8021 resin 35 parts, good corrosion resistance) △E=2.8 (meet the requirements), gloss loss rate after washing 28% (meet the requirements), gloss loss rate after polishing 15% (over standard) Example three Table dry 15min, real dry 52h (catalyst 4 parts, alcohol ester twelve 6 parts, drying speed is slow) 144h rust area 5% (BF-8021 resin 15 parts, poor corrosion resistance) △E=4.2 (over standard), gloss loss rate after washing 40% (over standard), gloss loss rate after polishing 20% (over standard) Example four Table dry 9min, real dry 38h (catalyst 4 parts, drying speed is good) 200h no rust (BF-8021 resin 44 parts, good corrosion resistance) △E=2.5 (meet the requirements), gloss loss rate after washing 12% (meet the requirements), gloss loss rate after polishing 20% (over standard) Example five Table dry 18min, real dry 60h (catalyst 4 parts, alcohol ester twelve 2 parts, drying speed is the slowest) 120h rust area 10% (BF-8021 resin 12 parts, poor corrosion resistance) △E=3.8 (over standard), gloss loss rate after washing 32% (over standard), gloss loss rate after polishing 25% (over standard) Example six Table dry 10min, real dry 40h (catalyst 4 parts, alcohol ester twelve 2 parts, drying speed meets the requirements) 200h no rust (BF-8021 resin 43 parts, good corrosion resistance) △E=2.9 (meet the requirements), gloss loss rate after washing 28% (meet the requirements), gloss loss rate after polishing 8% (meet the requirements)

[0137] According to the test results above, example six performs best in corrosion resistance, hiding power, drying speed, and cost balance, and is the best choice;

[0138] In an environment of 25-30℃, the drying speed of the paint film surface is 10min, and the real drying time is 40min; in the neutral salt spray test for 200h, the paint film does not rust or fall off; in the artificial aging test for 200h, the paint film has no cracking, powdering, blistering, falling off, rusting, etc., color difference △E=2.9, gloss loss rate after washing 28%, and gloss loss rate after polishing 8%, which fully meets the requirements of cast pipe paint for outdoor storage for 2 years without rusting, gloss loss, or falling off, etc.

[0139] The above examples are only used to illustrate the technical method of the present application but not limit the present application. Although the present application is described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical method of the present application can be modified or equivalently replaced without departing from the spirit and scope of the technical method of the present application.

Claims

1. A method for preparing highly weather-resistant solvent-free polyurethane from polycarbonate diol, characterized in that, This high weather-resistant solvent-free polyurethane comprises the following raw materials in parts by weight: 10-45 parts of BF-8021 waterborne ultra-fast drying anticorrosive resin, 5-25 parts of BF-9011 acrylic dispersion, 1-5 parts of carbon black special dispersant, 1-8 parts of carbon black, 5-25 parts of light calcium carbonate, 5-20 parts of barium sulfate, 5-15 parts of dimethyl ethanolamine, 5-20 parts of propylene glycol methyl ether, 1-6 parts of waterborne paint special anti-settling agent, 0.2-2 parts of defoamer, 1-4 parts of waterborne paint special drying agent, 1-6 parts of alcohol ester dodecyl, and 0-40 parts of water.

2. The method for preparing high weather-resistant solvent-free polyurethane from polycarbonate diol according to claim 1, characterized in that, Specifically, the following steps are included: Step 1: Weigh out BF-8021 water-based ultra-fast drying anticorrosive resin, BF-9011 acrylic dispersion, carbon black special dispersant, carbon black, light calcium carbonate, barium sulfate, dimethyl ethanolamine, propylene glycol methyl ether, defoamer, water-based paint special anti-settling agent, water-based paint special drying agent, alcohol ester twelve, and water, and set aside. Step 2: Add BF-8021 water-based ultra-fast drying anti-corrosion resin to the paint mixing tank, start stirring, control the speed at 500-700 r / min, and adjust the pH to 8-9 using dimethylethanolamine in two stages. Step 3: Add carbon black-specific dispersant and carbon black in three stages, controlling the stirring speed at 500-700 r / min, and stir for 10 min; Step 4: Add barium sulfate, light calcium carbonate and water-based paint anti-settling agent in sequence, and control the dispersion speed in stages at 1500-1800 r / min, and stir for 30 min; Step 5: The sand mill uses a "three-pass grinding method" to grind the raw material to a fineness of less than 25 μm. Before sand milling, 3% propylene glycol methyl ether is added to adjust the rheological properties. Step 6: In the paint mixing tank, add BF-9011 acrylic dispersion, 97% propylene glycol methyl ether, defoamer, water-based paint drier, and alcohol ester twelve, and adjust the viscosity with water. Step 7: Central control inspection. If it passes the inspection, filter and package it.

3. The method for preparing high weather-resistant solvent-free polyurethane from polycarbonate diol according to claim 2, characterized in that, In step two, the pH is adjusted in two stages. Initially, the amount of dimethylethanolamine added is controlled at 70% of the total amount, and the pH is adjusted to 7.

5. After the BF-8021 water-based ultra-fast drying anticorrosive resin is completely wetted, the remaining 30% amine is added to bring the pH to 8.5, and the mixture is stirred for 5 minutes.

4. The method for preparing high weather-resistant solvent-free polyurethane from polycarbonate diol according to claim 2, characterized in that, In step three, the carbon black-specific dispersant is added in three stages: First stage: add 60% of the total amount of dispersant and stir at 500 r / min for 2 min; Second stage: add carbon black and disperse at 600 r / min for 5 min; Third stage: add the remaining 40% of the dispersant and maintain stirring at 700 r / min for 3 min.

5. The method for preparing high weather-resistant solvent-free polyurethane from polycarbonate diol according to claim 2, characterized in that, In step four, barium sulfate is added first, and the mixture is stirred at 800 r / min for 3 min. Then, light calcium carbonate and water-based paint anti-settling agent are added simultaneously, and the stirring speed is maintained at 800 r / min for 5 min. Finally, the dispersion speed is controlled in stages: first stage: stirring at 1500 r / min for 8 min; second stage: stirring at 1800 r / min for 14 min.

6. The method for preparing high weather-resistant solvent-free polyurethane from polycarbonate diol according to claim 2, characterized in that, In step five, a "three-pass grinding method" is adopted: the first pass is coarse grinding using 0.8mm zirconium beads; the second pass is medium grinding using 0.6mm zirconium beads; the third pass is fine grinding using 0.3mm zirconium beads; after each pass of grinding, a sample is taken to measure the fineness, and the bead diameter is changed after the standard is met.

7. The method for preparing high weather-resistant solvent-free polyurethane from polycarbonate diol according to claim 2, characterized in that, In step six, the defoamer is added in three batches: 70% is added after grinding, 20% is added during the paint mixing stage, and 10% is added before packaging. The water-based paint-specific drying agent is mixed with alcohol ester twelve in a 1:1 ratio before being added dropwise at a rate of 2-3 mL / min, and the water bath temperature is increased to 30±2℃; the viscosity adjustment is changed to a three-stage water replenishment: water replenishment after grinding for 20s, water replenishment after grinding for 30s, and water replenishment before packaging for 35s.

8. The method for preparing high weather-resistant solvent-free polyurethane from polycarbonate diol according to claim 2, characterized in that, In step seven, filtration is performed using a double-layer filter cloth with 200 mesh and 5μm thickness.

Citation Information

Patent Citations

  • Superfast-drying, anti-adhesion, and anticorrosion paint for casting pipes

    CN105778672A

  • Aqueous cast pipe outer wall anticorrosive coating and preparation method and application thereof

    CN109294408A